Global variation of soil microbial carbon-use efficiency in relation to growth temperature and substrate supply - Qiao, Yang; Wang, Jing; Liang, Guopeng; Du, Zhenggang; Zhou, Jian; Zhu, Chen; Huang, Kun; Zhou, Xuhui; Luo, Yiqi; Yan, Liming; Xia, Jianyang (Scientific reports, 2019)
Soil microbial carbon-use efficiency (CUE), which is defined as the ratio of growth over C uptake, is commonly assumed as a constant or estimated by a temperature-dependent function in current microbial-explicit soil carbon (C) models. The temperature-dependent function (i.e., CUE = CUE 0 + m × ( T − 20)) simulates the dynamic CUE based on the specific CUE at a given reference temperature (i.e., CUE 0 ) and a temperature response coefficient (i.e., m ). Here, based on 780 observations from 98 sites, we showed a divergent spatial distribution of the soil microbial CUE (0.5 ± 0.25; mean ± SD ) at the global scale. Then, the key parameters CUE 0 and m in the above equation were estimated as 0.475 and − 0.016, respectively, based on the observations with the Markov chain Monte Carlo technique. We also found a strong dependence of microbial CUE on the type of C substrate. The multiple regression analysis showed that glucose influences the variation of measured CUE associated with the environmental factors. Overall, this study confirms the global divergence of soil microbial CUE and calls for the incorporation of C substrate beside temperature in estimating the microbial CUE in different biomes.